Product Variety on Customer Satisfaction: The Mediating and Moderating Role of Price Perception and Service Quality - Lazuardi, Sofyan; Wahjoedi, Tri; Emmywati, Emmywati; Rahardjo, Kusuma Adi; Nugroho, Agung Dwi (LPPPIPublishing, 2025)
This study examines the mediation and moderation effects of price perception and service quality on the relationship between product variety and customer satisfaction in the automotive spare parts retail area. In this study, a quantitative approach was used and data were collected from 80 customers of the BC Waru Sidoarjo store using a questionnaire distributed through Google Forms. Statistical analysis was performed by SEM SmartPLS3 software. The results indicate that the factors of pricing perception, service quality, and product variety are interrelated in a very intricate way and can have a huge effect on customer satisfaction. This finding pinpoints the need for an integrated and holistic approach towards improving customer satisfaction. It will help management come up with more efficient ways of improving customer loyalty for competitive advantage in the market by understanding the dynamics of these elements and their interlinkages. It also offers a glimpse into the important interrelations that exist among the variables of key concern, while duly underscoring the need for clarity in understanding those factors that may affect the level of satisfaction on the part of customers from the motor vehicle spare parts sector.